Pemesinan Nonkonvensional Plasma Arc Cutting - Al Antoni Akhmad (Jurnal Rekayasa Mesin, 2009)
In machining process known 2 kind machining process, conventional machining and nonconventional machining. Plasma Arc Cutting is example nonconventional machining.Plasma Arc Cutting so many used in all of kind industry that use metal as raw material. In Plasma Arc Cutting there are many kind of torch. Every torch has spesifik characteristic and spesific funtion.